Alex Rider. Ark angel : the graphic novel - Johnston, Antony; Horowitz, Anthony, 1955- (Candlewick Press, 2020)
Teenage spy Alex Rider's chance encounter with the son of billionaire Nikolei Drevin sends him on a collision course into the heart of an international plot to destroy the Pentagon. It all has to do with a revolutionary space hotel named Ark Angel, which could become a weapon of catastrophic power.